Surgical removal of tonsils and risk of COVID-19: a nested case–control study using data from UK Biobank and AMORIS Cohort - Yanping Yang; Kejia Hu; Karin Modig; Maria Feychting; Imre Janszky; Niklas Hammar; Fang Fang; Zhe Zhang; Dang Wei (BMC Medicine)
Abstract Background To investigate the association between surgical removal of tonsils and risk of COVID-19 with different severity. Methods Through a nested case–control study during January 31st to December 31st 2020, including 58,888 participants of the UK Biobank, we investigated the association of tonsillectomy with the future risk of mild and severe COVID-19, using binomial logistic regression. We further examined the associations of such surgery with blood inflammatory, lipid and metabolic biomarkers to understand potential mechanisms. Finally, we replicated the analysis of severe COVID-19 in the Swedish AMORIS Cohort (n = 451,960). Results Tonsillectomy was associated with a lower risk of mild (odds ratio [95% confidence interval]: 0.80 [0.75–0.86]) and severe (0.87 [0.77–0.98]) COVID-19 in the UK Biobank. The associations did not differ substantially by sex, age, Townsend deprivation index, or polygenic risk score for critically ill COVID-19. Levels of blood inflammatory, lipid and metabolic biomarkers did, however, not differ greatly by history of surgical removal of tonsils. An inverse association between tonsillectomy and severe COVID-19 was also observed in the AMORIS Cohort, primarily among older individuals (> 70 years) and those with ≤ 12 years of education. Conclusions Surgical removal of tonsils may be associated with a lower risk of COVID-19. This association is unlikely attributed to alterations in common blood inflammatory, lipid and metabolic biomarkers.